Oviposition deterrent activity of different botanicals against Spodoptera litura (Lepidoptera: Noctuidae) in soybean: OVIPOSITION DETERRENT ACTIVITY OF BOTANICALS AGAINST SPODOPTERA LITURA IN SOYBEAN - NAVYA MATCHA; BAND S S; SUNDAR B; A K BHOWMICK (Journal of Oilseeds Research, 2019)
Tobacco caterpillar, Spodoptera litura (F.) is a polyphagous pest widely distributed in south east Asia which is an economically important pest as it can cause 25 to 100 per cent crop loss by defoliation. Heavy use of insecticides caused it to gain resistance over almost all groups of insecticides. Use of botanicals is a conventional approach for pest management as it is a two-tier approach by being eco-friendly and also manages the pest population. Therefore, the present study was carried out to determine the ovicidal and repellent activities of botanicals viz., Datura leaf extract 5%, Annona leaf extract 5%, Marigold leaf extract 5%, Neem oil 5%, Pongamia oil 5% and Eucalyptus oil 2% against S. litura in soybean. The study revealed that the Eucalyptus oil 2 % was least preferred for oviposition as the number of eggs laid in this treatment were 71.20, out of which 31.50 per cent eggs hatched and it also possessed the lowest oviposition index 0.20, followed by Neem oil 5% as the number of eggs laid in this treatment were 157.20, among which 46.28 per cent eggs hatched having an oviposition index of 0.23. Hence, the results indicate that eucalyptus oil and neem oil were least preferred, hence the botanicals are reliable source for eco-friendly management of S. litura in soybean.